Are executive functions engaged in language switching? The role of language proficiency - García González, Elisabet; Lahdenranta, Sonja; Lehtonen, Minna (CAMBRIDGE UNIV PRESS, 2026)
We investigated whether executive functions (EFs) are engaged in bilingual language control in Finnish speakers with different degrees of Swedish language experience and proficiency, including early bilinguals, late high-proficiency bilinguals and low-proficiency learners of Swedish. In an online experiment, language switching was measured with a cued naming (CN) paradigm, and a Simon task was used to assess EF performance. Following the skill-learning (task specificity) hypothesis, we expected that language switching may be automatized and no longer rely on EFs in bilinguals with high language proficiency, but not for those with lower proficiency. Thus, we expected significant associations between the tasks in the lower proficiency participants only. Our results showed no CN switching-EF associations in the more experienced L2 speakers, but a significant association in lower-proficiency participants. This suggests that language switching engages EFs only in participants with lower proficiency in whom these processes are not yet automatized.